Polarization of Stakeholder Orientation Towards Geotourism Development in the Mount Slamet and Serayu Mountainous Areas, Central Java Province - Mafut Munajat; Ricky Avenzora; Dudung Darusman; Sambas Basuni (Jurnal Manajemen Hutan Tropika, 2022)
The success of geotourism development is strongly influenced by the orientation (perceptions, motivations and preferences) of the stakeholders. An aim of the study was to analyze the polarization of stakeholder orientation towards geotourism development in the Mount Slamet and Serayu Mountainous areas, Central Java Province. Research instrument used a closed-ended questionnaire following the scoring pattern of "One Score One Indicator Scoring System”. The sample of respondents was 8 stakeholder groups with a total of 1,252 respondents. The characteristics of the stakeholder was analysed by quantitative descriptive, while the indication of the polarization of the stakeholder orientation was analyzed by using the one way Anova statistical test. Results indicated that the polarization of stakeholder orientation had a positive direction and scale of polarization was strong. This conditions showed that there is a gap in the value of stakeholder orientation which makes the performance of geotourism development less than optimal. It is necessary to improve the quality of collaboration and cooperation so that there is no polarization in the orientation between stakeholders to achieve the sustainable geotourism development.